PEMBUATAN MESIN SENSOR CUCI TANGAN KEPADA MASYARAKAT DI DESA TANJUNG ANOM, RT. 06/RW.02 BANJARNEGORO, MERTOYUDAN KAB. MAGELANG, JAWA TENGAH - Slamet Widodo; Ahsan, Ahmad Nur; Desetya Alsava Kurniawan; Firman Yudha Pratama (PPM Sdirjianbang Akademi Militer, 2023)
The composition of the villagers of Tanjung Anom, Rt. 06 / Rw.02 Banjarnegoro, Mertoyudan Magelang regency, Central Java consists of students, private sector employees and farmers. For the community during the covid-19 pandemic, the need for facilities to support health procedures is very necessary in line with the increasing spread of the covid-19 virus and the existence of PPKM from the government. The need for prokes support tools is certainly felt to be more expensive because of the higher users and enthusiasts in the context of virus prevention. This is a problem experienced by residents of Tanjung Anom Mertoyudan. Defense Electrical Engineering Study Program Akmil, with all the energy and skills to contribute to the people of Tanjung Anom to provide a practical and simple solution in preventing the transmission of the covid-19 virus. The activity of making automatic sensor machines for free in the framework of community service of the Akmil Defense Electrical Engineering Study Program managed to meet the target where there were one area RT Tanjung anom residents who could use automatic hand washing tools. The implementation of hand washing machine with automatic sensor was carried out for two days, where the first day managed to make 3 tools and the second day managed to make 2 sensor-based hand washing tools. In the manufacture of this tool there are no obstacles and barriers faced, so that people can easily use hand washing tools without any obstacles